2017
DOI: 10.1111/1440-1681.12696
|View full text |Cite
|
Sign up to set email alerts
|

GRK2/β‐arrestin mediates arginine vasopressin‐induced cardiac fibroblast proliferation

Abstract: Cardiac fibrosis is a pathological feature commonly found in hearts exposed to haemodynamic orneurohormonal stress. Elevated levels of arginine vasopressin (AVP) are closely associated with the progression of heart failure and could be an underlying cause of cardiac fibrosis. The aim of this study is to characterize the effect of AVP on neonatal rat cardiac fibroblasts (NRCFs) and to illustrate its signalling mechanism. The proliferative effect of AVP was assessed by methylthiazolyldiphenyl-tetrazolium assay a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…V 1A R Mediates AVP-Induced Inflammation. To determine which subtypes functionally mediate AVP-induced IL-6 production, mRNAs for V 1A receptor were detected only by reverse transcription-PCR in NRCFS (Chen et al, 2017). More importantly, the V 1A receptor selective inhibitor SR49059 efficiently blocked the AVP-induced IL-6 expression with 2.35 6 0.46 nM, IC 50 (n 5 3, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…V 1A R Mediates AVP-Induced Inflammation. To determine which subtypes functionally mediate AVP-induced IL-6 production, mRNAs for V 1A receptor were detected only by reverse transcription-PCR in NRCFS (Chen et al, 2017). More importantly, the V 1A receptor selective inhibitor SR49059 efficiently blocked the AVP-induced IL-6 expression with 2.35 6 0.46 nM, IC 50 (n 5 3, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GRK in inflammation and inflammatory disease is an evolving area of research (Packiriswamy and Parameswaran, 2015), but there is little information on the inflammatory regulation of GRK2 in hearts. Our previous study has shown that AVP enhances the survival of H9c2 myoblasts (Zhu et al, 2013), proliferation of rat smooth muscle (Zhang et al, 2016), and cardiac fibroblasts (Chen et al, 2015(Chen et al, , 2017) via a GRK2/b-arrestin1/ERK 1/2 -dependent pathway. The present study investigated the effect of AVP on IL-6 production in neonatal rat cardiac fibroblasts (NRCFs) and the relative impact of the GRK2-dependent signaling on this effect.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition to b-arrestin, increasing nontraditional functions of GPCR kinases (GRKs) have also been discovered beyond their original function for GPCR desensitization. Zhu et al (2012) found that Gi-biased b 2 -adrenergic receptor signaling links GRK2 upregulation to heart failure, and that GRK2/b-arrestin signaling mediates the proliferation of cardiac fibroblast induced by arginine vasopressin (Chen et al, 2017) and cell survival evoked by hypoxia (Zhu et al, 2013). In this special issue, Dr. Weizhong Zhu's laboratory found that GRK2 mediates arginine vasopressin-induced interleukin-6 production via nuclear factor kB p65 signaling in neonatal rat cardiac fibroblasts (Xu et al, 2017).…”
mentioning
confidence: 99%